Thermophysical properties of magnesium arsenide with atomistic simulation methods - Gunay, Seckin D. (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
A classical interionic potential for the Buckingham potential model was developed for magnesium arsenide (Mg3As2). Potential parameters were fitted to available experimental and first-principles data in the literature. They were implemented in classical molecular dynamics programs, and static properties such as lattice constant, bulk modulus, shear modulus, Young's modulus, elastic constants, Poisson's ratio and anisotropy factor were obtained at 0 K. Lattice constants, linear thermal expansion coefficients, heat capacities, self-diffusion coefficients for each axis, bulk moduli and radial distribution functions were calculated from room temperature up to the melting point. A superionic phase transition was observed. The superionic phase transition and the melting temperature points were found similar to 1505 K and similar to 1700 K by two-phase simulation box method, respectively. This method was used for the first time to determine the superionic phase transition temperature. Lattice parameter and bulk modulus were also calculated by the first-principles method. All the calculated data displayed an agreement with the available experimental and first-principles data in the literature. The present parameters of Buckingham potential provide a good description of magnesium arsenide (Mg3As2) crystal.
Keywords: Magnesium arsenide; Lattice parameter; Superionic; Mechanical property; Diffusion; TOTAL-ENERGY CALCULATIONS; MOLECULAR-DYNAMICS; CRYSTAL; PROGRAM; Chemistry; Physics